2019
DOI: 10.1021/acsami.8b22659
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Responsive Hydrophobic Silica Nanoparticle Ultrasound Contrast Agents Directed by Phospholipid Phase Behavior

Abstract: In this paper, we report ultrasonically-active nanoscale contrast agents that behave as thermometric sensors through phase change in their stabilizing phospholipid monolayer. Phospholipid-stabilized, hydrophobic mesoporous silica nanoparticles (P@hMSNs) are known to interact with high intensity focused ultrasound (HIFU) to promote cavitation at their surfaces, which can be used for both imaging and therapy. We show that the lateral lipid phase behavior of the phosphocholine lipid dictates the acoustic contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…Cavitation onset peak negative pressures for hydrophobic MSNs coated with different lipids with different tail lengths (right). Adapted from reference [ 79 ], Copyright 2019, American Chemical Society …”
Section: Gas Stabilizing Nanoparticles (Gsns) As Exogenous Nuclei For Acoustic Cavitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cavitation onset peak negative pressures for hydrophobic MSNs coated with different lipids with different tail lengths (right). Adapted from reference [ 79 ], Copyright 2019, American Chemical Society …”
Section: Gas Stabilizing Nanoparticles (Gsns) As Exogenous Nuclei For Acoustic Cavitationmentioning
confidence: 99%
“…In the last decade, we have witnessed rapid growth in the field with the development of several different GSNs. These nanoparticles have already been utilized in different applications to detect and treat cancer [ 40 , 48 , 80 , 104 ] and others such as cardiovascular diseases [ 73 , 79 , 87 ]. These studies have also significantly increased our understanding of the cavitation inception by nanoparticles.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Phospholipid-stabilized hydrophobic MSNs could promote cavitation at their surfaces and MB formation under US exposure, which led to contrast enhancement. When the lipids were in the gel phase below their melting temperature, p@hMSN generated detectable MBs after exposure to US, indicating that the lipid was effective for MB generation and contrast enhancement [ 590 ]. Paris et al designed MSNs that displayed submicrometer-sized cavitation nuclei and evaluated their extravasation and biodistribution using US-induced inertial cavitation.…”
Section: Reviewmentioning
confidence: 99%
“…In this paper, we report a unique contrast agent that is designed to induce cavitation on the surface at low laser fluence and thus impart a nonlinear PA response while also maintaining a strong PA response in the linear regime. Previously, we showed that hydrophobically modified mesoporous silica nanoparticles facilitate acoustic cavitation by stabilizing the formation of gas pockets on the surface. Here, gold nanorods with plasmon resonance in the near infrared (NIR) were coated first with silica and then covalently modified with hydrophobic alkyl chains. To impart dispersibility in aqueous solvents, the nanoparticles were resuspended with a monolayer of phospholipids (Figure ).…”
Section: Introductionmentioning
confidence: 99%